PRE - TREATMENT ANXIETY AND INTERFERON INDUCED DEPRESSION IN HEPATITIS C PATIENTS - Andleeb, Salma; Jahangir, Farhana; Shaheen, Nighat (Journal of Postgraduate Medical Institute, 2016)
Objective: To study the effect of pre-treatment anxiety on interferon induced depression in hepatitis C patients undergoing interferon treatment. Methodology: Interrupted time series design was used for this study to as -sess at pre, in 2 follow up visits (after 24th and 48th week) and after comple -tion of the treatment. The depression and anxiety of two groups of women (showing high and low pre-treatment anxiety score on the IPAT anxiety scale [PTAS]) was measured by the Siddiqui Shah Depression Scale (SSDS) and the IPAT Anxiety Scale. Female patients (n=57) being diagnosed for Hepatitis C and prescribed for interferon therapy were selected from three main hospitals of Peshawar, through convenience sampling technique. Results: The age range of the sample was from 35 to 65 years (54.51+5.11 years). Compared to 25 % of the patients having low pre-treatment anxiety scores, 32 % of the patients with higher pre-treatment anxiety score expe -rienced significant level of depression at week 24 and 48 during and after completion of the interferon treatment. Conclusion: Pre-treatment anxiety has significant effect on the levels of de-pression, hepatitis C patients experience during and after completion of the treatment.